Perogies and politics : Canada's Ukrainian left, 1891-1991 - Hinther, Rhonda L., 1974- (University of Toronto Press, 2018)
In Perogies and Politics, Rhonda Hinther explores the twentieth-century history of the Ukrainian left in Canada from the standpoint of the women, men, and children who formed and fostered it. For twentieth-century leftist Ukrainians, culture and politics were inextricably linked. The interaction of Ukrainian socio-cultural identity with Marxist-Leninism resulted in one of the most dynamic national working-class movements Canada has ever known. The Ukrainian left's success lay in its ability to meet the needs of and speak in meaningful, respectful, and empowering ways to its supporters' experiences and interests as individuals and as members of a distinct immigrant working-class community. This offered to Ukrainians a radical social, cultural, and political alternative to the fledgling Ukrainian churches and right-wing Ukrainian nationalist movements. Hinther's colourful and in-depth work reveals how left-wing Ukrainians were affected by changing social, economic, and political forces and how they in turn responded to and challenged these forces.
Keywords: Right and left (Political science) -- Canada -- History -- 19th century.; Right and left (Political science) -- Canada -- History -- 20th century.; Ukrainians -- Canada -- Politics and government -- 19th century.; Ukrainians -- Canada -- Politics and government -- 20th century.; HISTORY -- Canada -- General.; HISTORY / Canada / General; Right and left (Political science); Ukrainians -- Politics and government; Canada; 1800-1999; History